ADA FAKTOR YANG MEMENGARUHI HARGA JUAL BARANG MEWAH TINGGI PADA PRODUK BRAND COACH - Faradina, Selin; Milenia, Vindi (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
This study aims to analyze the factors that influence the high selling price of luxury goods on the Coach brand, because it has become a spotlight in global economic and business discussions. The main focus is directed at the role of consumer perception and brand strength in forming high selling prices. This study uses a descriptive qualitative approach with a literature study method and secondary data analysis obtained from annual reports, international business articles, and academic literature. The results of the study indicate that Coach's pricing strategy is not determined by production costs alone, but by consumer perceptions of brand image, social status, exclusivity and global supply chain. This study suggests that further researchers develop more studies related to the integration of consumer perception, supply chain strategy, and brand value in the context of strategic marketing with a global scope to enrich the literature on marketing and consumer behavior.